MITOLOGI SUKSESI PEREMPUAN DALAM IKLAN NIVEA VERSI â€œNEVER STOP CARINGâ€ - girsang, lasmery rm (SEMIOTIKA: Jurnal Komunikasi, 2019)
There are many kinds of functions of advertising; one of them can be used for campaigning human care. As represented through "Never Stop Caring" version from Nivea product, it is related to the mythology of woman succession. The women refer to successful figures in their respective fields. Using Roland Barthes's semiotics, this qualitative study analyzes six scenes becomes the units of analysis. From the results, it was found that the myth of the successful woman is not only seen from the work performance or position obtained, but also from support provided by people around. The representation of women's succession itself lies in the message conveyed by the figures who convey the message about support or motivation. In the end, the succession of women conveyed in these advertisements leads to mental or mind changes that can strengthen women in process of change.